Overcoming Segmentation in Social Policy? Comparing New Early Education and Childcare Efforts in Costa Rica and Uruguay - Martínez Franzoni, Juliana (2018)
During the late 2000s, Early Child Education and Care (ECEC) became a policy priority for several Latin American countries. Coherent with international ideas yet against the legacy of deep-seated segmentation, the new programs embraced universalist aims. Are countries able to achieve universalism? Why are some countries advancing more than others? This article addresses this question, exploring changes in the policy architectures and policy processes behind ECEC in Costa Rica and Uruguay – two regional leaders in these efforts. Based on document analysis and interviews with policymakers, we show that Uruguay advanced more decisively towards unification and explore why